A biodiversity assessment of bats (Chiroptera) in a tropical lowland rainforest of Central Amazonia, including methodological and conservation considerations - Sampaio, Erica M.; Kalko, Elisabeth Klara Viktoria; Bernard, Enrico; Rodríguez-Herrera, Bernal; Handley, Charles O. (Studies on Neotropical Fauna and Environment, 2003)
In our study of bat diversity in the Amazon Basin, we captured bats in undisturbed continuous forest and in forest fragments at the Biological Dynamics of Forest Fragments Project (BDFFP) near Manaus, Brazil, from January 1996 until July 1999. We recorded 72 species of bats in a sample of more than 7700 individuals caught during 29,900 mistnet hours in terra-firme forest. Species accumulation curves and mathematical estimates of species numbers based on the number of species captured with standardized methodology suggest that we sampled about 95% of the entire expected bat fauna of the area, including aerial insectivorous bats. Our results are similar to those of other mistnetting inventories of Amazonian bat assemblages in terms of species composition and number of species per bat family. Some species considered widespread in Central Amazonia and expected at our study site were not recorded. We interpret their absence as effects of sampling bias and of local ecological conditions. We know from acoustic monitoring (i.e., identification of bats by their echolocation calls) that our mistnet data are incomplete for aerial insectivorous species. We conclude that the development of comprehensive inventories of key vertebrate taxa such as bats derived from a combination of several standardized sampling procedures is essential to develop meaningful, conservation-oriented plans for land-use and management of protected areas.
Keywords: Chiroptera; Vertebrata